The Relationship Between Clinical Leadership Perceptions and Teamwork Attitudes: An Analysis in the Context of Emergency Healthcare Services - Yaren Kavraz Güney; Ahu Tuğba Karabulut (Acıbadem Üniversitesi Sağlık Bilimleri Dergisi, 2026)
Purpose:Clinical leadership is closely associated with teamwork effectiveness in emergency healthcare settings, where rapid decision-making, coordination, and communication are essential. The purpose of this study was to examine the relationship between clinical leadership perceptions and teamwork attitudes among healthcare professionals working in emergency healthcare services. Teamwork attitudes are examined within the framework of communication, mutual support, leadership, team structure and situation monitoring dimensions in this study.Methods: This study was conducted with a quantitative research design on 290 healthcare professionals who work in private hospitals and ambulance services in Istanbul. Data were collected using a structured questionnaire consisting of three sections: demographic and work-related questions, the Clinical Leadership Scale, and the Teamwork Attitudes Questionnaire. Frequency distribution analysis, confirmatory factor analysis, correlation, and regression analyses were performed on the collected data by using SPSS and AMOS.Results: Higher perceptions of clinical leadership were positively and significantly associated with all dimensions of teamwork attitudes, including communication, situation monitoring, mutual support, leadership, and team structure. Furthermore, the analysis revealed significant and positive results among these variables.Conclusions: The findings suggest that clinical leadership is closely associated with positive teamwork attitudes in emergency healthcare services. Strengthening clinical leadership competencies and promoting a teamwork-oriented culture may contribute to improving teamwork processes, healthcare quality, and patient safety.